Learning Methods for Accounting Students: Explore The Effectiveness of Traditional Learning and Laptop-Based Active Learning - Rizki Hamdani; Ayu Chairina Laksmi; Wirawan Hardinto (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
The main purpose of this study is to explore the effectiveness of Traditional Learning (TL) and Laptop-Based Active Learning (LAL) in the achievement of accounting students’ competence. This study is quantitative methods approach comprising of a systematic literature review, data analysis, and experimental studies on the two classes applying a different learning approach. Class A with 40 students applied the LAL approach, while class B with 38 students applied the TL approach. Students in the two classes received different treatments, but the question items tested were the same. This study also uses the independent samples t-test to analyze the hypotheses from the two data groups, both those using TL and LAL learning types. Overall, this study demonstrates that the accounting students’ learning achievement is higher when the class uses LAL approach instead of TL approach and that the LAL approach is better than the TL approach, especially on the Descriptive Statistics for Business course at Accounting Department, Islamic University of Indonesia.